2021
DOI: 10.3389/fnut.2021.654902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Interval and Continuous Exercise Training on Gastric Emptying, Appetite, and Adaptive Responses in Men With Overweight and Obesity

Abstract: Background/Objectives: Characterizing compensatory and adaptive responses to exercise assists in understanding changes in energy balance and health outcomes with exercise interventions. This study investigated the effects of a short-term exercise intervention (combining high intensity interval (HII) and continuous exercise) on (1) gastric emptying, appetite and energy intake; and (2) other adaptive responses including cardiorespiratory fitness, in inactive men with overweight/obesity.Methods: Fifteen men (BMI:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…intervention study with young obese men could not detect a difference in GE in response to a 4 week period of regular chronic low intensity exercise (Horner et al, 2021). Similarly, healthy un-trained adult males showed no difference in GE in a study comparing no exercise with acute 60 min low and high lower-body exercise before breakfast (Mattin et al, 2018).…”
Section: Lipidsmentioning
confidence: 85%
See 1 more Smart Citation
“…intervention study with young obese men could not detect a difference in GE in response to a 4 week period of regular chronic low intensity exercise (Horner et al, 2021). Similarly, healthy un-trained adult males showed no difference in GE in a study comparing no exercise with acute 60 min low and high lower-body exercise before breakfast (Mattin et al, 2018).…”
Section: Lipidsmentioning
confidence: 85%
“…A meta‐analysis from 2015 using data from 20 studies, mainly using a liquid bolus delivered pre‐exercise to measure GE, concluded that chronic low intensity exercise results in faster GE whilst high intensity exercise results in slower GE (Horner et al, 2015). However, an intervention study with young obese men could not detect a difference in GE in response to a 4 week period of regular chronic low intensity exercise (Horner et al, 2021). Similarly, healthy un‐trained adult males showed no difference in GE in a study comparing no exercise with acute 60 min low and high lower‐body exercise before breakfast (Mattin et al, 2018).…”
Section: Factors Affecting Gastric Emptyingmentioning
confidence: 99%
“…Intervention studies have also explored the link between physical activity and gastric emptying, with mixed results. Most studies have shown no effect on gastric emptying after four weeks to three months of moderate to vigorous intensity exercise 140,144,145 . However, in one study, three months of vigorous intensity exercise training did not affect gastric emptying, whereas gastric emptying was accelerated after six months 140 .…”
Section: Physical Activitymentioning
confidence: 99%